2010
DOI: 10.1007/s00018-010-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

SAM domain-dependent activity of PfTKL3, an essential tyrosine kinase-like kinase of the human malaria parasite Plasmodium falciparum

Abstract: Over the last decade, several protein kinases inhibitors have reached the market for cancer chemotherapy. The kinomes of pathogens represent potentially attractive targets in infectious diseases. The functions of the majority of protein kinases of Plasmodium falciparum, the parasitic protist responsible for the most virulent form of human malaria, remain unknown. Here we present a thorough characterisation of PfTKL3 (PF13_0258), an enzyme that belongs to the tyrosine kinase-like kinase (TKL) group. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
1
29
1
2
Order By: Relevance
“…Among these 22 ePKs are 8 enzymes that we previously reported as playing a crucial role in asexual proliferation: Pfmap-2 (PF11_0147) 9 , Pfnek-1 (PFL1370w) 10 , PfCK2 (PF11_ 0096) 11 , PfTKL3 (PF13_0258) 12 , Pfcrk-3 (PFD0740w) 13 , PfCLK1 (PF14_0431) 14 , PfCLK2 (PF14_0408) 14 and PfARK1 (PF13_0258) 15 . Others have provided reverse genetics evidence for essentiality of three additional ePKs, PfCDPK1 (PFB0815w) 16 , PfPKG (PF14_ 0346) 17 and PfPCDPK5 (PF13_0211) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these 22 ePKs are 8 enzymes that we previously reported as playing a crucial role in asexual proliferation: Pfmap-2 (PF11_0147) 9 , Pfnek-1 (PFL1370w) 10 , PfCK2 (PF11_ 0096) 11 , PfTKL3 (PF13_0258) 12 , Pfcrk-3 (PFD0740w) 13 , PfCLK1 (PF14_0431) 14 , PfCLK2 (PF14_0408) 14 and PfARK1 (PF13_0258) 15 . Others have provided reverse genetics evidence for essentiality of three additional ePKs, PfCDPK1 (PFB0815w) 16 , PfPKG (PF14_ 0346) 17 and PfPCDPK5 (PF13_0211) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…2, Table S1). PfTKL3 (PF13_0258), whose activity requires an accessory SAM domain mediating oligomerisation, is essential for asexual parasite proliferation and has recently been validated as a drug target through reverse genetics [95]. It is noteworthy that two other kinases related to TKLs, PfTKL1 (PFB050w) and PF11_0079, are both among the few proteins in the P. falciparum proteome that contain SAM domains, like PfTKL3 [95].…”
Section: The Tkl Groupmentioning
confidence: 99%
“…In IRAK4, interaction between the Glu in subdomain III and the 'Y' gatekeeper residue (instead of the K in subdomain II) stabilizes the active conformation. The presence of the 'Y' gatekeeper may underlie the maintenance of a weak activity of the KAM mutant, which, in PfTKL3, completely abolishes activity (Abdi et al, 2010) (see Discussion).…”
Section: In Vitro Activity Of Recombinant Pftkl2mentioning
confidence: 97%
“…Members of this family are absent from unicellular organisms such as yeast (Shiu & Bleecker, 2003) and Dictyostelium (Goldberg et al, 2006). We previously reported that the P. falciparum genome contains four sequences that cluster with TKLs from higher organisms, and provided a detailed characterization of one of these, PfTKL3 (PlasmoDB identifier PF13_0258/PF3D7_1349300) (Abdi et al, 2010). Here, we present the characterization of PfTKL2 (PlasmoDB identifier PF11_0220/PF3D7_1121300), a protein we identified as belonging to the RLK/Pelle family -quite an unusual observation for a unicellular organism.…”
Section: Introductionmentioning
confidence: 99%